2022
DOI: 10.1093/gbe/evac021
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Genetic History of the Maniq, a Primary Hunter-Gatherer Society

Abstract: The Maniq of southern Thailand is one of the last remaining practicing hunter-gatherer communities in the world. However, our knowledge on their genetic origins and demographic history is still largely limited. We present here the genotype data covering ∼2.3 million SNPs of eleven unrelated Maniq individuals. Our analyses reveal the Maniq to be closely related to the Semang populations of Malaysia (Malay Negritos), who altogether carry an Andamanese-related ancestry linked to the ancient Hòabìnhian hunter-gath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
(85 reference statements)
0
4
0
Order By: Relevance
“…More recently, and given their distinct genetic profiles, greater efforts to include and integrate more indigenous Malaysian and Thai hunter–gatherers in population genetic analyses have revealed that at least three waves of migration into the Malay peninsula are required in order to explain the observed genetic diversity, with the ancestors of the Semang group of contemporary hunter–gatherers probably representing the first inhabitants of the region (Aghakhanian et al, 2015 ; Lipson et al, 2018 ; McColl et al, 2018 ; Göllner et al, 2022 ). Likewise, a recent publication affirmed the deep genetic ancestry of several Punan groups living across North Kalimantan, Borneo.…”
Section: The Importance Of Hunter–gatherer Genetics Researchmentioning
confidence: 99%
“…More recently, and given their distinct genetic profiles, greater efforts to include and integrate more indigenous Malaysian and Thai hunter–gatherers in population genetic analyses have revealed that at least three waves of migration into the Malay peninsula are required in order to explain the observed genetic diversity, with the ancestors of the Semang group of contemporary hunter–gatherers probably representing the first inhabitants of the region (Aghakhanian et al, 2015 ; Lipson et al, 2018 ; McColl et al, 2018 ; Göllner et al, 2022 ). Likewise, a recent publication affirmed the deep genetic ancestry of several Punan groups living across North Kalimantan, Borneo.…”
Section: The Importance Of Hunter–gatherer Genetics Researchmentioning
confidence: 99%
“…More recently, and given their distinct genetic profiles, greater efforts to include and integrate more indigenous Malaysian and Thai hunter-gatherers in population genetic analyses have revealed that at least three waves of migration into the Malay peninsula are required in order to explain the observed genetic diversity, with the ancestors of the Semang group of contemporary hunter-gatherers likely representing the first inhabitants of the region (Aghakhanian et al 2015;Lipson et al 2018;McColl et al 2018;Göllner et al 2022). Likewise, a recent publication affirmed the deep genetic ancestry of several Punan groups living across North Kalimantan, Borneo.…”
Section: Paleoanthropological and Archaeological Evidence Had Traditi...mentioning
confidence: 99%
“…The KhonTai (TK) and ThaiMalay (AN) account for ~66% and 33% of the population, respectively, whereas the Maniq, one of the minor groups in the region, speak an Austroasiatic (AA) language. Maniq is one of the indigenous peoples of Southeast Asia (SEA) and probably descend from mid-Holocene hunter-gatherers [1][2][3], since they carry ancient genetic lineages [4,5]. Overall, there is evidence of a long history of human occupation of Southern Thailand [6], as attested by the diversification of population subsistence patterns, cultural artifacts of Paleolithic hunter-gatherers associated with the Hòabı `nhian archaeological tradition dated to ~27-38 thousand years ago (kya) [7], and human remains at Moh Khiew Cave in the Krabi Province (dated to ~26-8 kya) [8][9][10].…”
Section: Introductionmentioning
confidence: 99%